2020
DOI: 10.3934/publichealth.2020028
|View full text |Cite
|
Sign up to set email alerts
|

Ecological study on the penetration of induction heating cookers and birth outcomes in Japan

Abstract: About the Scientific CommitteesThree independent non-food Scientific Committees provide the Commission with the scientific advice it needs when preparing policy and proposals relating to consumer safety, public health and the environment. The Committees also draw the Commission's attention to the new or emerging problems which may pose an actual or potential threat.They are: the Scientific Committee on Consumer Safety (SCCS), the Scientific Committee on Health and Environmental Risks (SCHER) and the Scientific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 529 publications
(680 reference statements)
1
3
0
1
Order By: Relevance
“…Our results are partially consistent with those of a previous study showing no associations between maternal exposure to IF magnetic fields generated by electronic article surveillance systems during preg-nancy and PTB or birth weight [Khan et al, 2018]. Our results are in partial agreement with those of an ecological study at the prefectural level in Japan, which showed no correlation between the penetration of IH cookers and LBW (r = 0.60 in 2009 and r = 0.09 in 2014) [Sato et al, 2020].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our results are partially consistent with those of a previous study showing no associations between maternal exposure to IF magnetic fields generated by electronic article surveillance systems during preg-nancy and PTB or birth weight [Khan et al, 2018]. Our results are in partial agreement with those of an ecological study at the prefectural level in Japan, which showed no correlation between the penetration of IH cookers and LBW (r = 0.60 in 2009 and r = 0.09 in 2014) [Sato et al, 2020].…”
Section: Discussionsupporting
confidence: 92%
“…A cohort study in Finland found no association between IF magnetic fields emitted by electronic article surveillance systems and the risk of miscarriage, low birth weight (LBW), or preterm birth (PTB) [Khan et al, 2018]. A recent ecological study in Japan showed no significant correlation between the penetration of IH cookers and spontaneous fetal death rate, fetal death rate after the 22nd week of pregnancy, perinatal mortality rate, or LBW at the prefectural level [Sato et al, 2020].…”
Section: Introductionmentioning
confidence: 99%
“…Researchers [6] reported finding no effects of electronic article surveillance on miscarriage, premature birth, or reduced birth weight among women working in supermarkets. Other researchers [7] found no association between the penetration of household IH cookers and birth outcomes in an ecological study in Japan. The authors in [8] also found no association between the use of household IH cookers and delivery outcomes in a cohort study of pregnant women in Japan.…”
Section: Introductionmentioning
confidence: 81%
“…2020;15 3:381-383. DOI -https://doi.org/10.14300/mnnc.2020.15090 С ложилось мнение, что анатомо-гистологические изменения, нарушения структурноклеточной конструкции органов иммунной системы под влиянием электромагнитного поля связаны с адаптационной реакцией организма, развернутой во времени [1][2][3]. Специфические, ещё до конца не уточненные механизмы дестабилизирующего действия магнитных полей на молекулярном и клеточном уровнях жизнедеятельности сопровождаются и неспецифическими проявлениями структуры и функции органов иммуногенеза [4,5].…”
Section: Abstract: Variable Electromagnetic Fields Of Industrial Frequnclassified